2019
DOI: 10.1128/mcb.00175-19
|View full text |Cite
|
Sign up to set email alerts
|

A tel2 Mutation That Destabilizes the Tel2-Tti1-Tti2 Complex Eliminates Rad3ATR Kinase Signaling in the DNA Replication Checkpoint and Leads to Telomere Shortening in Fission Yeast

Abstract: In response to perturbed DNA replication, ATR (ataxia telangiectasia and Rad3-related) kinase is activated to initiate the checkpoint signaling necessary for maintaining genome integrity and cell survival. To better understand the signaling mechanism, we carried out a large-scale genetic screen in fission yeast looking for mutants with enhanced sensitivity to hydroxyurea. From a collection of ∼370 primary mutants, we found a few mutants in which Rad3 (ATR ortholog)-mediated phospho-signaling was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 73 publications
2
13
0
Order By: Relevance
“…2B). Though more severe, the similar defects in the DRC and the DDC have also been described in the previously reported tel2-C307Y mutant (1).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…2B). Though more severe, the similar defects in the DRC and the DDC have also been described in the previously reported tel2-C307Y mutant (1).…”
Section: Resultssupporting
confidence: 83%
“…The method for examining Rad3 phosphorylation of Mrc1-Thr 645 , Rad9-Thr 412 and Cds1-Thr 11 using the phosphor-specific antibodies has been described in our previously studies (1,12,43). The myc or HA tagged proteins was examined by Western blotting by using mouse monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CLK-2 (CLocK–biological timing–abnormality) impacts multiple cellular and developmental processes [ 21 – 23 ]. Its orthologs, from yeast to human, regulate telomere length and DNA damage response [ 24 27 ]. Additionally, biochemical studies demonstrated that the human counterpart of CLK-2, TELO2, functions as a scaffold for the assembly of a protein complex, the R2TP complex, which mediates the assembly of phosphatidylinositol 3-kinase-related kinases (PIKKs), such as ATM and ATR (critical for DNA damage response) and, importantly, the NMD kinase SMG1 [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%